2020
DOI: 10.3390/su13010085
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Geo-Strategic Railway Freight Network in Brazil Using GIS

Abstract: The sustainable development of geo-strategic transport networks plays a key role to meet the current expansion of the demand for commerce and economic growth. In this paper, a new geo-strategic railway network for freight services is designed with the purpose of meeting the needs of current and future demands for freight transport in the state of Santa Catarina, South Brazil. The freight flows of bulk cargo, containers, and refrigerated and liquid cargo observed in 2005 and 2015 and expected for 2023 have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…In the problem posed, container flows are considered as multi-product flows, therefore, on the multigraph, some vertices are connected by several equally directed arcs. There are also some arcs on the multigraph, along which container flows follow in both directionsthese are arcs (3, 4) and (4, 3); (5, 6) and (6, 5); (14,15) and (15,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the problem posed, container flows are considered as multi-product flows, therefore, on the multigraph, some vertices are connected by several equally directed arcs. There are also some arcs on the multigraph, along which container flows follow in both directionsthese are arcs (3, 4) and (4, 3); (5, 6) and (6, 5); (14,15) and (15,14).…”
Section: Resultsmentioning
confidence: 99%
“…The problem of distributing container train flows can be represented as a problem of a multicommodity flow of minimum cost, which boils down to determining the optimal option for transporting goods in a network setting [13]. The multiproduct transport problem is of great practical importance and was used by a number of authors to optimize railway network routes [14][15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…Liimatainen et al [19] reported that the use of longer and heavier vehicles (LHVs) for various commodities in road freight transport can ensure considerable savings in traffic volume and emissions. Isler et al [20] designed a visualized geostrategic railway network for freight services to solve multiple freight type transport problems. Carrone et al [21] found that the use of autonomous vehicles (AVs) in regular vehicle (RV) operation areas will reshape the transport system and greatly improve capacity utilization.…”
Section: Related Workmentioning
confidence: 99%
“…The ISO tank container is a large container for fluids or powders, and it has considerable flexibility; in fact, its transport can take place by road, rail or ship, with the possibility of combining the three ways, with advantages in terms of costs and transport safety. It consists of a single cylindrical tank, called "tank body", arranged inside a rectangular steel frame; furthermore, the whole structure is in accordance with ISO standards, in particular ISO 1496/3 [20,21]. The most common dimensions are a length of 6.058 m, a height of 2.591 m and standard width of 2.438 m. Furthermore, the tare generally varies between 3000 and 5000 kg; by tare, we mean the mass of the empty tank container in its normal operating conditions, i.e., including all accessories and associated equipment.…”
Section: Tank Container For Foodstuffmentioning
confidence: 99%